2019
DOI: 10.3390/jcm8050689
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Ureteric Stent Removal and Occurrence of Urological Complications after Kidney Transplantation: A Systematic Review and Meta-Analysis

Abstract: Implanting a ureteric stent during ureteroneocystostomy reduces the risk of leakage and ureteral stenosis after kidney transplantation (KTx), but it may also predispose to urinary tract infections (UTIs). The aim of this study is to determine the optimal timing for ureteric stent removal after KTx. Searches were performed in EMBASE, MEDLINE Ovid, Cochrane CENTRAL, Web of Science, and Google Scholar (until November 2017). For this systematic review, all aspects of the Cochrane Handbook for Interventional System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 40 publications
5
36
0
2
Order By: Relevance
“…[16] Our ongoing practice of removing the stent after 21 days or earlier in infection has been backed by a review by Visser et al who also estimate 21 days post transplant to likely be the ideal time based on current knowledge. [25] Twenty-three percent of our patients developed asymptomatic bacteriuria in the rst month which is comparable to other reports. Most transplant centers treat asymptomatic bacteriuria after KT.…”
Section: Discussionsupporting
confidence: 90%
“…[16] Our ongoing practice of removing the stent after 21 days or earlier in infection has been backed by a review by Visser et al who also estimate 21 days post transplant to likely be the ideal time based on current knowledge. [25] Twenty-three percent of our patients developed asymptomatic bacteriuria in the rst month which is comparable to other reports. Most transplant centers treat asymptomatic bacteriuria after KT.…”
Section: Discussionsupporting
confidence: 90%
“…In general, stent-related complications are especially seen in patients when the stent is left for a longer period in situ [2,3,20]. Patel et al [1••] also demonstrated a better quality of life in patients with early stent removal.…”
Section: Dj-stents Considerationsmentioning
confidence: 99%
“…In most centres, stents are removed between 2 and 6 weeks after transplantation [1••, 20]. Since a later stent removal shows a higher risk for stent-related complications, some authors advocate an early removal of the stent after 3 weeks [20]. Although stentrelated complications may be reduced by an early stent removal, there still is some concern about higher rates of urinary leak and ureteric obstruction when stents are removed too early.…”
Section: Dj-stents Considerationsmentioning
confidence: 99%
“…The timing of ureteral stent removals is especially important in patients with renal transplant. A shorter stent dwell time of 3 weeks as opposed to 6 weeks decreased the risk of UTIs in these patients [ 23 ]. In a prospective study of 103 renal transplant patients, Isiris could be used with ease and convenience on the ward, ICU and outpatient department and showed a cost saving for the hospital [ 24 ].…”
Section: Discussionmentioning
confidence: 99%